Identifikasi Efektifitas Faktor Pada Proses Kerja Engineering Kontraktor di Proyek Konstruksi Secara Jarak Jauh di Masa Pandemi Covid-19 - Ryan Faza Prasetyo (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2020)
Covid-19 pandemic affected all of the country. Not only affected public’s health, pandemic also massively affected the social state and country’s economy. Some of the country already entering the recession, not limited to Indonesia. One of contributed sector in Indonesia’s economy is construction industry sector which this sector now in declining growth. The implementation of Work-from-Home (WFH) in construction company is one of many ways so the economy and construction sector in Indonesia keep on the track. On contrary, contractor’s engineering process in project need intensed communication with stakeholder and direct monitoring so it’s against the WFH concept. This research aim to know the effectivity of every contractor’s engineering process in project during pandemic. The result of research found that quantity survey process, making of method statement, and job safety analysis are effective enough to do with WFH concept. While the process of site construction progress calculation, design fixation, and shopdrawing process and approval are not effective to do wih WFH concept.